2013
DOI: 10.1063/1.4829635
|View full text |Cite
|
Sign up to set email alerts
|

Electro-caloric effect in (Ba1−xCax)(Zr0.05Ti0.95)O3: A lead-free ferroelectric material

Abstract: Electro-caloric effect in lead-free (Ba1−xCax)(Zr0.05Ti0.95)O3 ferroelectric ceramics has been studied for x = 0.05, 0.08, and 0.10. The electro-caloric coefficient as high as 0.253 K mm/kV has been obtained near tetragonal-to-cubic phase transition for x = 0.08. This value is nearly the same as observed in lead-based ferroelectric materials. The higher value of electro-caloric coefficient at x = 0.08 is attributed to the higher polarization flexibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
38
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(46 citation statements)
references
References 29 publications
6
38
2
Order By: Relevance
“…Polynomial of fourth order is fitted (R 2 = 0.9997, 1, 0.9999, and 0.9999) for electric field of 10, 14.5, 18, and 21.5 kV/cm, respectively. A number of researchers have used similar type of polynomial fitting to estimate the electrocaloric effect in ferroelectric ceramics . It is clearly observed that as electric field increases, saturation polarization also increases in accordance with the discussion provided earlier.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Polynomial of fourth order is fitted (R 2 = 0.9997, 1, 0.9999, and 0.9999) for electric field of 10, 14.5, 18, and 21.5 kV/cm, respectively. A number of researchers have used similar type of polynomial fitting to estimate the electrocaloric effect in ferroelectric ceramics . It is clearly observed that as electric field increases, saturation polarization also increases in accordance with the discussion provided earlier.…”
Section: Resultssupporting
confidence: 74%
“…Electrocaloric effect (adiabatic temperature change Δ T ) and the isothermal entropy change Δ S can be estimated using the following Maxwell's relationships: ΔT=TρCE2E1)(dPsdTdE ΔS=E2E1)(dPsdTdE where ρ and C are the density and specific heat capacity, respectively. For similar type of composition (Ba 0.9 Ca 0.1 )(Zr 0.05 Ti 0.95 )O 3 , the absolute value of specific heat capacity is reported by Singh et al . in the temperature range of 25–140°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Singh et al 13 reported recently rather large electrocaloric responsivity coefficient (DT/DE) of 0.253 K mm/kV in (Ba 1Àx Ca x )(Zr 0.05 Ti 0.95 )O 3 with x ¼ 0.08 near tetragonal-to-cubic phase transition. However, only 0.15 K mm/kV was reported in (1 À x)BaZr 0.2 Ti 0.8 O 3 -x Ba 0.7 Ca 0.3 TiO 3 compounds for x ¼ 0.3.…”
mentioning
confidence: 99%
“…Since a giant ECE of ∆T max = 12K was obtained in PbZr 0.95 Ti 0.05 O 3 thin film in 2006 [1], the researches on ECE boom in various ferroelectric ceramics [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. However, large amount of high power devices working in a small space will induce local high temperature, which degrades the performance of electronic devices and may even lead to complete failure.…”
Section: Introductionmentioning
confidence: 99%